Benefits and risks of antiplatelet therapy for moyamoya disease: a systematic review and meta-analysis - Liu, Tingting; Qin, Mingzhen; Xiong, Xuejiao; Li, Tingting; Feng, Luda; Lai, Xinxing; Gao, Ying (Frontiers in Neurology, 2023)
Background: Moyamoya disease (MMD) is a leading cause of stroke in children and young adults, whereas no specific drugs are available. Antiplatelet therapy (APT) has been considered as a promising treatment option, but its effectiveness remains controversial. Therefore, we aimed to comprehensively evaluate the benefits and risks of APT for MMD. Methods: We systematically searched PubMed, Embase and Cochrane Library electronic databases from their inception to June 30, 2022, and conducted a systematic review. All-cause mortality was taken as the primary outcome. Results: Nine studies that enrolled 16186 patients with MMD were included. Results from a single study showed that APT was associated with lower mortality (hazard ratio (HR) = 0.60; 95% confidence interval (CI) [0.50 to 0.71]; p < 0.01) and improved bypass patency after surgical revascularization (HR = 1.57; 95% CI [1.106 to 2.235]; p < 0.05). Results of the meta-analysis showed that APT reduced the risk of hemorrhagic stroke (HR = 0.47; 95% CI [0.24 to 0.94]; p < 0.05) but neither reduced the risk of ischemic stroke (HR = 0.80; 95% CI [0.33 to 1.94]; p = 0.63) nor increased the proportion of independent patients (RR = 1.02; 95% CI [0.97 to 1.06]; p = 0.47). Conclusion: Current evidence showed that APT was associated with a reduced the risk of hemorrhagic stroke in MMD patients, but did not reduce the risk of ischemic stroke or increase the proportion of independent patients. There was insufficient evidence about the benefit of APT on survival and postoperative bypass patency after surgical revascularization. However, the results should be interpreted cautiously because of the limited number of studies.